2010
DOI: 10.1111/j.1745-6584.2010.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Salmonella enterica in Clay Columns Comparing Two Manure Application Methods

Abstract: Transfer of zoonotic bacterial pathogens through intact soil columns was monitored in an outdoor lysimeter over 36 d. Manure spiked with Salmonella enterica serovar Senftenberg was applied to either the soil surface or injected 0.08 m into the soil to compare leaching associated with the two manure application methods. The highest concentrations of S. enterica (up to 60,000 S. enterica CFU/mL) were detected on Day 1 in the first drainage samples, with measurable but declining concentrations persisting for 10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Slurry injection increased the leaching of phage, E. coli, and Enterococcus species significantly compared to surface application and, for E. coli, with respect to both culturable cells and DNA (Table 3). Bech et al (27) reported that the average proportion of Salmonella enterica leached was 6.1% after injection and 0.6% after surface application on a silt loam soil, although the difference was not significant due to high variability among replicates. Similarly, significantly more phage leached from intact sandy clay loam soil cores exposed to natural weather conditions when raw slurry was injected rather than being surface applied (67).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slurry injection increased the leaching of phage, E. coli, and Enterococcus species significantly compared to surface application and, for E. coli, with respect to both culturable cells and DNA (Table 3). Bech et al (27) reported that the average proportion of Salmonella enterica leached was 6.1% after injection and 0.6% after surface application on a silt loam soil, although the difference was not significant due to high variability among replicates. Similarly, significantly more phage leached from intact sandy clay loam soil cores exposed to natural weather conditions when raw slurry was injected rather than being surface applied (67).…”
Section: Resultsmentioning
confidence: 99%
“…Slurry is usually applied to agricultural fields by surface application or, increasingly, by subsurface injection at 6-to 10-cm soil depth to reduce nuisance odor and NH 3 volatilization from the applied slurry (23,24,25). These two application methods may represent different risks for leaching of nutrients and microorganisms as a result of the difference in slurry-soil contact (21,26,27).…”
mentioning
confidence: 99%
“…The soil cores were excavated from the field site Slaeggerup, near the city of Roskilde, Denmark, as described by Bech et al (10). Briefly, the soil cores were randomly taken within a square of 4 m by 16 m. Fifteen soil cores were collected from the Ap horizon by applying steady-state weight pressure on the top of stainless steel cylinders (15 cm in diameter, 30 cm in height).…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the functional relations between the leaching of 16S rRNA genes and leaching of total P, dissolved P and particulate P reduced major axes were fitted (Webster, ). The values of leaching of 16S rRNA genes were positively skewed and so were transformed to logarithms (log 10 ) (Bech et al ., ) prior to estimation of the reduced major axes. Intercepts and slopes of the functional relations were determined from the reduced major axes and the corresponding 95% confidence intervals were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Transport of bacteria through soil depends on several factors such as soil type, irrigation or rainfall intensity, properties of the manure and vegetation (e.g. Entry et al, 2000;Bech et al, 2011). Groundwater wells contaminated with Escherichia coli (E. coli) have been found in Denmark (Brüsch & Rosenberg, 2008).…”
Section: Introductionmentioning
confidence: 99%